2011
DOI: 10.1007/s12011-011-9198-3
|View full text |Cite
|
Sign up to set email alerts
|

“Free” Copper: A New Endogenous Chemical Mediator of Inflammation in Birds

Abstract: For acceptance of any chemical agent as an endogenous chemical mediator of inflammation, the agent in question must fulfill some biological requirements which are (a) it should be ubiquitously present in tissues in inactive form, (b) it should be activated during process of inflammation whose increase should be identifiable, (c) it should induce or amplify some events of inflammation, (d) there must be some natural inhibitor of such active form in tissues, (e) it should be able to induce inflammatory reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…In vivo studies, high dietary copper can inhibit the serum, hepatic [ 24 – 27 ] and nephritic [ 28 ] antioxidase activities in ducklings, and induce oxidative stress in the brain [ 29 , 30 ] and spleen [ 31 ] of chickens. Also, it has been reported that intradermal injection of 2% CuSO 4 solution in the chicken can increase oxygen-derived free radicals, result in tissue damage and increase vascular permeability [ 32 ]. In in vitro studies, Cu and Cu compounds can cause oxidative stress via the production of ROS in human epithelial lung (A549) cells [ 33 ] and brain microvascular endothelial cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies, high dietary copper can inhibit the serum, hepatic [ 24 – 27 ] and nephritic [ 28 ] antioxidase activities in ducklings, and induce oxidative stress in the brain [ 29 , 30 ] and spleen [ 31 ] of chickens. Also, it has been reported that intradermal injection of 2% CuSO 4 solution in the chicken can increase oxygen-derived free radicals, result in tissue damage and increase vascular permeability [ 32 ]. In in vitro studies, Cu and Cu compounds can cause oxidative stress via the production of ROS in human epithelial lung (A549) cells [ 33 ] and brain microvascular endothelial cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%